The Impact of PT Vale's Investment on the Sorowako Village Community Nuha District 2019-2024 - Achmad; Amalia Syahda , Syalsa Bila (Kybernology : Journal of Government Studies, 2025)
The impact of PT Vale’s investment on the community of Sorowako Village, Nuha District, during the 2019–2024 period focuses on the socio-economic effects arising from the company’s investment activities, including increased income, expanded employment opportunities, and the development of local businesses. This study employs a qualitative method, with data collected through in-depth interviews, observation, and documentation. The findings indicate that the presence of PT Vale has made a significant contribution to community economic growth, particularly through increased trade and service activities, as well as business opportunities generated by the high demand from company employees. However, during the COVID-19 pandemic in 2021, community incomes declined due to activity restrictions and workforce reductions. Overall, PT Vale’s investment has played a positive role in improving local living standards, although sustainability strategies are still needed to ensure that the benefits are equitably distributed and can be sustained over the long term.